Case Studies in Mentoring Community College Faculty - Markus Pomper; Kathy Arcangeli; Jala Daniel (Academic Chairpersons Conference Proceedings, 2016)
This interactive session explores ways in which an academic division at a community college developed a program of faculty development and evaluation. We will discuss teaching evaluations for faculty, mentoring in preparation for tenure, and the support system provided to mentors.
Keywords: Faculty development; mentoring; tenure; changing expectations